2014
DOI: 10.1080/13218719.2014.960027
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention Deficit Disorder and Aggressive Behaviour: An Exploration of Relationships between Brown Attention-Deficit Disorder Scales and the Aggression Questionnaire

Abstract: . (2015). Adult attention deficit disorder and aggressive behaviour: an exploration of relationships between Brown Attention-Deficit Disorder Scales and the Aggression Questionnaire. Psychiatry Psychology and Law, 22 (3), 407-416. Adult attention deficit disorder and aggressive behaviour: an exploration of relationships between Brown Attention-Deficit Disorder Scales and the Aggression Questionnaire AbstractAggressive and violent behaviour is often associated with a diagnosis of attention-deficit hyperactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Considering that rs686 is a functional SNP located in the promoter region of the DRD1 gene and its A allele is linked with an increased transcriptional gene activity compared with the G allele [ 47 ], a difference in the DRD1 density number may occur in the tested cohort compared with the general population. Since these receptors mediate aggressive behaviour [ 9 , 10 ], this hypothesis is supported by a previous study reporting higher levels of aggressive behaviour in this cohort of prisoners when compared with university students [ 43 ]. The DRD2 genetic variant did not show any genetic association with a measurement of aggression through the AQ in accordance with a previous study looking at DRD2 rs1800479’s (located in the downstream of the gene) association with criminal behaviour and self-reported aggression in violent prison inmates [ 48 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Considering that rs686 is a functional SNP located in the promoter region of the DRD1 gene and its A allele is linked with an increased transcriptional gene activity compared with the G allele [ 47 ], a difference in the DRD1 density number may occur in the tested cohort compared with the general population. Since these receptors mediate aggressive behaviour [ 9 , 10 ], this hypothesis is supported by a previous study reporting higher levels of aggressive behaviour in this cohort of prisoners when compared with university students [ 43 ]. The DRD2 genetic variant did not show any genetic association with a measurement of aggression through the AQ in accordance with a previous study looking at DRD2 rs1800479’s (located in the downstream of the gene) association with criminal behaviour and self-reported aggression in violent prison inmates [ 48 ].…”
Section: Discussionsupporting
confidence: 73%
“…Since attention-deficit/hyperactivity disorder is one of the most disrupted metacognitive traits in prisoners [ 43 ], Brown Attention-Deficit Disorder Scales (BADDS) [ 44 ] were administered to this cohort by one of the authors (Byrne, a clinical and forensic psychologist) to assess executive function via measurement of Activation (organising/prioritising), Attention (focussing, sustaining and shifting attention to tasks), Effort (alertness, maintaining effort and speed for processing), Emotion/Affect (managing emotions and frustrations) and Memory (using working memory and recall testing) as previously described [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our research team has the track record to navigate studies through the ethics approval process, as evidenced by the feasibility studies and publication outcomes [ 7 , 53 ]. This research will be carried out in accordance with the Declaration of Helsinki [ 44 ] and the Australian National Statement on Ethical Conduct in Research Involving Humans [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Inmate Behaviour Observation Scale (IBOS): A measure of prisoner aggression and violence based on inmate case notes, in preparation/forthcoming) which are the most common measure of aggression in prison studies. The IBOS has been found to significantly correlate with both the Aggression Questionnaire (AQ) and the Brown’s Attention Deficit Disorder Scales (BADDS) [ 7 ], and given that the AQ and the BADDS are also significantly correlated [ 53 ], this adds to its construct validity.…”
Section: Outcomes {12}mentioning
confidence: 99%
“…A Greek study found significant correlations between the WURS and the total and all subscale scores of the AQ (Giotakos et al, 2005). A Hungarian study measured ADHD with the Adult Self-Report Scale and found significant differences between the ADHD- and ADHD+ groups on the AQ total, physical, anger, and verbal, but not the hostility subscales (Bacskai et al, 2012), and an Australian study that measured ADHD with the Brown Attention-Deficit Disorder Scales found a significant correlation with the AQ total score (Byrne et al, 2015). A study of college students with and without ADHD found that the ADHD group had significantly higher levels of both trait and state anger.…”
Section: Aggression and Adhdmentioning
confidence: 99%